Evaluating the diffusive equilibrium models: Comparison with the IMAGE RPI field‐aligned electron density measurements. Issue 6 (5th June 2014) - Ozhogin, P.; Song, P.; Tu, J.; Reinisch, B. W.
Abstract The diffusive equilibrium models that are widely used by the space physics community to describe the plasma densities in the plasmasphere are evaluated with field‐aligned electron density measurements from the radio plasma imager (RPI) instrument onboard the IMAGE satellite. The original mathematical form of the diffusive equilibrium model was based on the hydrostatic equilibrium along the magnetic field line with the centrifugal force and the field‐aligned electrostatic force as well as a large number of simplifying approximations. Six free parameters in the mathematical form have been conventionally determined from observations. We evaluate four sets of the parameters that have been reported in the literature. The evaluation is made according to the equatorial radial distance dependence, latitudinal dependence at a given radial distance, and the combined radial and latitudinal dependences. We find that the mathematical form given in the diffusive equilibrium model is intrinsically incompatible with the measurements unless another large number of free parameters are artificially introduced, which essentially changes the nature of a theoretical model to an empirical model.